The framing of ‘Muslim women hijab’ issue in Malaysia: A content analysis of Malaysian mainstream newspapers - Tan, Ching Ting (2023)
Hijab-wearing is a common phenomenon in Malaysia, yet the rule of banning hijab still exists. This paper is an investigation of the portrayal of ‘Muslim Women Hijab’ issue in Malaysian news media including The Star, New Straits Times and Malay Mail using Goffman’s (1974) Framing approach. Specifically, this study aims (1) to examine how Malaysian mainstream newspapers frame ‘Muslim Women Hijab’ issue in news reporting and (2) to determine the frames used in the representation of Muslim hijabbing issue in the Malaysian news reports. A qualitative content analysis has been applied to 40 news items published from November 2017 until September 2020. The analysis identifies the news frames following the scale of Semetko and Valkenburg (2000), including responsibility, conflict, human interest, morality, liberation, and discrimination frames. The findings reported that newspapers cover the hijab issue with varying degrees of intensity and prominence. It was found that although the responsibility frame was the most prevalent frame across the Muslim hijab news stories, the aspects highlighted varied. The liberation frame gained the least attention. The findings are also beneficial for government policymakers and political leaders in Malaysia for future policy formulation towards the hijab-wearing. Journalists are able to enhance their way to cover the hijab issue coverage and the public get the knowledge on how the Malaysian news media frame the Muslim hijab issue.